Child Care Management from The Point Of View Of The Book Of Ihya' 'Ulūm Al-Dīn In Malaysia - Asri, Nik Muhamad Amal Mohd; Rahman, Mohd Nazri Abdul; Sulaiman, Abdul Muhsien; Muhith, Abd; Sholeh, Muh Ibnu; Fathurro'uf, Muhammad (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2024)
This research investigates the management of child care from the perspective of the Book of Ihya' 'Ulūm al-Dīn in Malaysia. Against the backdrop of a country rich in Islamic heritage and cultural diversity, this study explores the relevance of the concepts in the Book of Ihya' 'Ulūm al-Dīn in the context of childcare in Malaysia. The library research research method is used to collect, evaluate and analyze related literature, including relevant primary and secondary sources. The results of the analysis show that concepts such as religious education, character formation, and the development of moral values in the Book of Ihya' 'Ulūm al-Dīn have a strong suitability to the life of Malaysian society. This research also highlights the important role of parents, teachers and society in implementing Islamic principles in child care management practices. The implications of the findings of this research include the need to integrate the values of the Book of Ihya' 'Ulūm al-Dīn in educational policies and community development programs to form a generation with noble and responsible morals. In conclusion, this research provides an in-depth understanding of the contribution of Islamic teachings in the management of child care in Malaysia and paves the way for further research in understanding the practical application of these values in society.